A Theoretical Development of the Gender Embodiment of Enrichment: A Study of Gender Norms in Enrichment and Factors Related to Enrichment in a Sample of the Swedish Working Population - Hagqvist, Emma (Front Sociol, 2021)
Enrichment is a phenomenon described as the synergistic and beneficial effects of participating in both work and private life. Far too few studies have acknowledged the role of gender in enrichment. By applying a gender theoretical approach, this article has two aims; first, we aim to study the role of gender in enrichment by examining the factorial structure of enrichment in men and women; secondly, we aim to study the relationship between enrichment and work and private life factors in an approximately representative sample of the Swedish working population. A multigroup confirmatory factor analysis with measurement in variance was performed and this resulted in a two-factor solution for enrichment for both men and women, representing the two directions of enrichment: work-to-life enrichment (WLE) and life-to-work enrichment (LWE). Factor loadings differ across genders, indicating that men and women construct and value items of enrichment differently. Next, linear mixed models were used to answer the second aim. Results show that gendered cultural norms in work and private life manifest in the relationship between factors in the work and home sphere and enrichment. Factors in work and private life with more or less masculine or feminine epithets relate differently to WLE and LWE for men and women. The main conclusion is that masculine and feminine norms are embodied in the values and experiences of enrichment and factors related to enrichment.